Os médicos do Programa Mais Médicos: olhares estrangeiros sobre nossas mazelas sociais e médico-sanitárias - Alves da Silva, Quelen Tanize [UNIFESP] (2019)
This thesis presents a study focused on "giving voice" to the doctors participating in the Programa Mais Médicos (PMM). The study wanted to make visible the stories of the subjects who, in their work contexts, contribute to the accomplishment of this policy. The research was based on the following question: what senses do the doctors participating in the program give to a policy like PMM? Because it is an investigation focused on the micropolitical dimension of health policies, in its implementation in singular contexts, we opted for the adoption of a qualitative approach that privileged the narratives of experiences of the doctors participating in the program. Through them, it was possible to compose a partial "photograph" of the Brazilian health system, cut in some of the more expressive elements in the narratives - daily life and working conditions, political crossings and political and administrative obstacles in the PMM and Unified Health System (SUS), the medicalsocial maladies of our country, the violence in the territories and the practices of medicine - circumstantiated at the moment of their experiences, somehow reverberating the well-known limits of the full realization of SUS as health policy. These doctor’s narratives and reflections are presented as "a foreign look" about our country, from their experiences in the singular contexts of the Basic Health Units where they were allocated. A foreign look that often sheds light on aspects of our life we somehow "incorporate into the landscape," which do not bother us anymore, and, worse, seem to have lost the power to provoke our astonishment and indignation capacity.